An image enhancement algorithm of video surveillance scene based on deep learning. Issue 3 (24th June 2021) - Shen, Wei‐wei; Chen, Lin; Liu, Shuai; Zhang, Yu‐Dong
Abstract: Target enhancement is the most important task in a video surveillance system. In order to improve the accuracy and efficiency of target enhancement, and better deal with the subsequent recognition, tracking, behaviour understanding and other processing of targets, a deep learning‐based image enhancement algorithm for video surveillance scenes is proposed. First, the super‐resolution reconstruction of the image is carried out through the image super‐resolution reconstruction method based on the hybrid deep convolutional network to improve the sharpness of the image. Then, for the reconstructed video surveillance scene image, the watershed image enhancement algorithm based on morphology and region merging is used to realize the enhancement of the video surveillance scene image. Deep learning algorithms can improve the accuracy of image enhancement through iterative calculations. Experimental results show that after image enhancement in daytime, night and noisy video surveillance scenes, the maximum enhancement difference rate is less than 0.5%, the cross‐linking degree is close to 1, and the average image enhancement time is less than 1.3 s. It can realize image enhancement of video surveillance scenes and improve the image clarity of the video surveillance scene.